Improved Population-Based Clinical Outcomes of Patients with Atrial Fibrillation by Compliance with the Simple ABC (Atrial Fibrillation Better Care) Pathway for Integrated Care Management: A Nationwide Cohort Study - Yoon, Minjae; Yang, Pil-Sung; Jang, Eunsun; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Kim, Jong-Youn; Sung, Jung-Hoon; Pak, Hui-Nam; Lee, Moon-Hyoung; Joung, Boyoung; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2019)
Background An integrated care approach might be of benefit for clinical outcomes of patients with atrial fibrillation (AF). This study evaluated whether compliance with the Atrial fibrillation Better Care (ABC) pathway for integrated care management (“A” Avoid stroke; “B” Better symptom management; “C” Cardiovascular risk and Comorbidity optimization) would improve population-based clinical outcomes in a nationwide AF cohort.Methods and Results From the Korea National Health Insurance Service database, a total of 204,842 nonvalvular AF patients were enrolled between January 1, 2005 and December 31, 2015. Patients that fulfilled all criteria of the ABC pathway were defined as the “ABC” group, and those who did not were the “Non-ABC” group.Over a mean follow-up of 6.2 ± 3.5 years, the ABC pathway compliant group had lower rates of all-cause death (0.80 vs. 2.72 per 100 person-years, p < 0.001) and the composite outcome of “death, ischemic stroke, major bleeding, and myocardial infarction” (2.34 vs. 5.92 per 100 person-years, p < 0.001) compared with the Non-ABC compliant group. Adjusted Cox multivariable regression showed that the ABC group had a significantly lower risk of all-cause death (adjusted hazard ratio [HR] 0.82; 95% confidence interval [CI], 0.78–0.86) and the composite outcome (adjusted HR 0.86; 95% CI, 0.83–0.89). With the increasing numbers of ABC pathway criteria fulfilled, the risk of all-cause death and composite outcome were progressively lowered.Conclusion In the first study of a nationwide population cohort, we show that compliance with the simple ABC pathway is associated with improved clinically relevant outcomes of patients with AF. Given the high health care burden associated with AF, such a streamlined holistic approach to AF management should be implemented, to improve the care of such patients.
Keywords: ABC pathway; atrial fibrillation; comorbidities; integrated care; outcomes